AB162. A novel “SSS+f” nephrometry score system to evaluate the technical complexity of nephron-sparing surgery - Zhang, Shudong (Transl Androl Urol, 2016)
OBJECTIVE: For the complex and technical nature of tumor exposure, tumor resection, and renal reconstruction involved in partial nephrectomy, a detailed understanding of renal tumor anatomy is necessary for comprehensive preoperative surgical protocols. We have developed a novel nephrometry scoring system (3S+f nephrometry score) to quantify the anatomical characteristics of renal masses on computerized tomography/magnetic resonance imaging. We aimed to propose this simple scoring system to evaluate the technical complexity of partial nephrectomy. METHODS: We retrospectively evaluated 100 patients with contrast-enhanced CT imaging who underwent laparoscopic partial nephrectomy consecutively between January 2014 and October 2015. The “SSS+f” nephrometry score is based on four critical and reproducible anatomical features of solid renal masses. Of the four components three are scored on a 1, 2 or 3-point scale with the 4(th) indicating the quantity and quality of the perinephric fat which put great influence on the technical difficulty is scored on 0 or 1-point scale. The “SSS+f” nephrometry score consists of SIZE (tumor size as intrarenal maximal diameter), SITE (tumor location including lateral/lower pole, medial/upper pole, hilar/endophytic), SIDE (distance of tumor deepest side to the collecting system or sinus or the main renal artery or vein). Moreover, perinephric fat (f) which is sticky or thick is assigned to tumors that evaluate technical difficulty of mobilize the kidney and isolate the renal tumor. RESULTS: The “SSS+f” nephrometry scoring system accurately classified the complexity of 100 consecutive tumors undergoing laparoscopic partial nephrectomy at our institution by single surgeon. Tumor complexity according to nephrometry score was assessed as low in 18 (18%), moderate in 48 (48%) and high-complexity group in 34 (34%). There were no significant differences with respect to EBL, transfusion rate, or postoperative complications among the three groups. Postoperative renal functional outcomes were similar among the three groups. Only mean operative time was significantly different with different group. The median warm ischemic time (WIT) was also significantly different in the low- versus high-complexity group but was similar between the moderate- and high-complexity groups. CONCLUSIONS: Standardized reporting of renal tumor size, site and side is essential for decision making and effective comparisons in nephron-sparing surgery. The “SSS+f” nephrometry score is a reproducible and simple classification system that quantitates the anatomic features of renal masses. This novel approach provides a simple and easy tool for meaningful comparisons of renal masses in clinical practice.